ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI TERINTEGRASI PADI – TERNAK SAPI POTONG DI KECAMATAN KAHU KABUPATEN BONE - Ahmad Zailan (Universitas Muhammadiyah Makassar, 2022)
ABSTRACTAnalysis Of Production And Integrated Farm Income Of Rice-Beef Cattle In Kahu sub-district, bone district. Supervised by Syafiuddin and Arifin Fattah. This study aims to analyze the production costs, income levels and profits of rice-cattle integrated farming in Kahu District, Bone Regency. The population in this study were the community of rice farmers as well as beef cattle breeders in Kahu District, amounting to 4356 people. Determination of the sample in this study using the Slovin technique which was then followed by a stratified random sampling technique by selecting the farmer community as well as beef cattle breeders in each village based on the stratum level. The number of samples in this study were 68 people. The data analysis used is descriptive and quantitative by using the income analysis method Based on the results of the analysis of production and income levels, the total cost value is Rp. 24.298.623., With a total rice production of 13,791 kilograms, the total beef cattle production is worth 337.29 kilograms. Income level of Rp. 67.019.143., With an R / C Ratio of 1.31 which indicates that farming with an integrated system is profitable to implement.Keywords: integrated farming, production, income, rice, beef cattle.